Application of the Participatory Rural Appraisal (PRA) Model in Policy Formulation through Village Consultation Deliberations in Walesi District Jayawijaya Regency - Irmayani Misrah; Ayu Anggraini Tambunan; Tukijan Tukijan; Usman Wenda (ITB AAS Indonesia Surakarta, 2024)
This study explores the application of the Participatory Rural Appraisal (PRA) Model in the Village Deliberation in Walesi District, Jayawijaya Regency, Papua Pegunungan Province, with a focus on community participation in local decision making. Qualitative methods were used to explore how PRA influenced the policy formulation process in four villages: Jagara, Tulima, Apenas, and Pawekama. This research was carried out involving District Heads, Village Heads and community leaders as the main informants. The data collection process used in-depth interviews and participatory observation, with the aim of identifying patterns of community participation in the Village Consultation Conference, as well as observing the impact of PRA implementation on local decisions. The collected data was analyzed thematically to explore the challenges faced in implementing PRA and understand the extent to which communities are involved in various stages of planning, implementation, utilization of results, and evaluation of local policies. The results of this research indicate that PRA has the potential to strengthen community participation in decision making. Public participation can be seen from the perspective of Arnstein's ladder of participation, which distinguishes various levels of participation ranging from simple information to full control over policy. These findings provide in-depth insight into how PRA can be used as a tool to improve the quality of community participation in the context of decentralization policy in Papua Pegunungan Province. Practically, this research provides recommendations for local governments and non-government organizations in increasing the effectiveness of the Village Deliberation through the PRA approach. These recommendations include increasing capacity and understanding of PRA for local stakeholders, strengthening communication mechanisms between stakeholders, and increasing transparency and accountability in the decision-making process. Thus, this research not only contributes to the literature on community participation in decision making, but also provides practical guidance for implementing participatory policies in remote areas such as Jayawijaya Regency, Papua Pegunungan Province.